(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
Taking into account the great amount of high-potassium tuffs, the opportunity of open elaboration and waistless production, it is possible to organize the production of chlorineless potassium fertilizers in Vanadzor. The observations have proved that these sorts after some processes can be used as a fertilizer without any ecological damage to the environment. That is why it is necessary to have more detailed and systematic observations and organize the production.